2017
DOI: 10.1002/jrs.5156
|View full text |Cite
|
Sign up to set email alerts
|

Raman spectroscopy as a tool for magnesium estimation in Mg‐calcite

Abstract: Despite their strong Raman scattering and importance in several applications in the geological and biological sciences, Mg‐calcites have not been thoroughly investigated by Raman spectroscopy. In this study, we investigated whether Raman spectra of carbonates are sensitive to the structural and chemical changes occurring when Mg2+ substitutes Ca2+ in the calcite lattice. Different carbonate samples with variable Mg content (from 0 to 20 mol% MgCO3) of biological and inorganic origin have been first beamed unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
41
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(48 citation statements)
references
References 52 publications
3
41
0
4
Order By: Relevance
“…In abiogenic aragonites with known fluid conditions, we found a clear dependence of Raman peak width on Ar , an observation that is not confounded by other factors, including temperature, Mg/Ca, pH, and [CO tors such as trace element variability to have some influence, our Raman results from abiogenic aragonites and the JCp-1 coral can be explained by Ar alone. Nevertheless, future investigations of controls on Raman spectra of corals skeleton will be useful, for instance in checking for positive correlations between ν 1 FWHM and wavenumber that would potentially indicate an effect of Mg/Ca (Bischoff et al, 1985;Perrin et al, 2016;Borromeo et al, 2017). We found no such relationships in either our Porites or Acropora analyses (p > 0.05, r 2 < 0.01 in both cases).…”
Section: Discussionmentioning
confidence: 49%
“…In abiogenic aragonites with known fluid conditions, we found a clear dependence of Raman peak width on Ar , an observation that is not confounded by other factors, including temperature, Mg/Ca, pH, and [CO tors such as trace element variability to have some influence, our Raman results from abiogenic aragonites and the JCp-1 coral can be explained by Ar alone. Nevertheless, future investigations of controls on Raman spectra of corals skeleton will be useful, for instance in checking for positive correlations between ν 1 FWHM and wavenumber that would potentially indicate an effect of Mg/Ca (Bischoff et al, 1985;Perrin et al, 2016;Borromeo et al, 2017). We found no such relationships in either our Porites or Acropora analyses (p > 0.05, r 2 < 0.01 in both cases).…”
Section: Discussionmentioning
confidence: 49%
“…[8] Near-infrared spectroscopy has been performed on all carbonate minerals of calcite structure. [9] However, to date, five natural carbonate minerals of calcite structure have been extensively studied by Raman spectroscopy, which include calcite, [1,[10][11][12][13][14][15] magnesite, [1,[12][13][14]16,17] siderite, [1,2,12,14,16] rhodochrosite, [12,14,18] and smithsonite, [12,14,19] and two synthetic carbonate compounds of calcite structure, CdCO 3 [12] and NiCO 3 , [12] have been studied to a lesser extent. It was noted by Rutt and Nicola [12] that synthetic CoCO 3 affords a poor Raman spectrum in which only two bands could be observed with certainty.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively however, Boulard et al [2] proposed that perhaps significant variation in the relative wavenumbers of phonons involving C-O bonds might be observed because Raman shifts might not be attributed to the slight length variation of the C-O bonds, but rather might be controlled by the bonding environment, that is, the potential variation around the CO 3 polyhedra. To date, Bischoff et al, [13] Rividi et al, [1] Boulard et al, [2] Perrin et al, [17] and Boromeo et al [18] have shown that the C-O phonons do shift in relative wavenumber with respect to divalent cations such as Ca 2+ , Mg 2+ , and Fe 2+ in the solid-solution series calcite-magnesite, calcite-siderite, and sideritemagnesite. With this in mind, Raman spectra are examined and interpreted for all eight naturally occurring carbonate minerals of calcite structure to investigate the effects on ionic radii and nearest neighbor (M-O) influences on phonon shifts for this group of minerals to facilitate a Raman spectroscopic model for the identification and discrimination of the calcite-group minerals.…”
Section: Introductionmentioning
confidence: 99%
“…While it remains theoretically possible for other fac- tors such as trace element variability to have some influence, our Raman results from abiogenic aragonites and the JCp-1 coral can be explained by Ar alone. Nevertheless, future investigations of controls on Raman spectra of corals skeleton will be useful, for instance in checking for positive correlations between ν 1 FWHM and wavenumber that would potentially indicate an effect of Mg/Ca (Bischoff et al, 1985;Perrin et al, 2016;Borromeo et al, 2017). We found no such relationships in either our Porites or Acropora analyses (p > 0.05, r 2 < 0.01 in both cases).…”
Section: Discussionmentioning
confidence: 57%